Tricuspid valve septal displacement cutoff value for mortality risk following biventricular repair in Ebstein anomaly - Dicky Fakhri; Pribadi Wiranda Busro; Budi Rahmat; Salomo Purba; Radityo Prakoso; Chaisari Maria M. Turnip; Alyarosa Taqwaariva (Annals of Pediatric Cardiology)
Background: Surgical intervention is the definitive treatment for Ebstein anomaly, offering both biventricular and nonbiventricular repair options. The objective of this study is to identify a specific cutoff value for tricuspid septal leaflet displacement, which will be a crucial factor in determining the selection of a surgical approach with lower mortality risk in biventricular repair. Methods and Results: This is a retrospective cohort study of consecutive patients with Ebstein anomaly undergoing surgical intervention at the National Cardiovascular Center Harapan Kita from January 2010 to December 2023. A total of 83 patients with Ebstein anomaly were treated surgically; 43 of those underwent biventricular repair, whereas the remaining underwent nonbiventricular repair. Echocardiography was performed, and the Great Ormond Street Echocardiography score was calculated. Several risk factors were identified and stratified for patients with biventricular repair (n = 43). Tricuspid septal leaflet displacement was measured for each patient, and there was a statistically significant higher mortality risk directly proportional to higher displacement in patients with biventricular repair (P < 0.05). A cutoff value of 43.5 mm/m² for the tricuspid septal leaflet displacement is the best predictor of mortality risk in biventricular repair with 83.3% sensitivity and 93.3% specificity. Conclusions: In patients with Ebstein anomaly undergoing a biventricular repair, mortality rates are significantly elevated in patients with a higher tricuspid septal leaflet displacement distance. The results of the study indicated that the mortality risk in biventricular repair can be predicted based on the tricuspid septal leaflet displacement distance using a cutoff value of 43.5 mm/m².